Exploring the Interplay Between Global Brand Image and Store Design: An Expert Review and Thematic Analysis of Apple and LEGO Stores in China - gong, pingwei; Abd Manan, Mohd Shahrudin; binti Zainudin, Norzalina (Environment and Social Psychology, 2025)
The rapidly evolving “New Retail” landscape is reshaping how global brands connect with consumers, yet the links between store design, hedonic value, and brand image remain underexplored. Existing studies often treat global brand identity and localized retail strategies separately, leaving a gap in understanding how physical stores can balance global consistency with local cultural resonance. To address this gap, this study examines the interplay between global brand image and localized store design, highlighting the mediating role of hedonic value to develop a conceptual framework. Twelve expert interviews were conducted with professionals in interior design, visual merchandising, marketing, and retail operations, and findings were triangulated with a literature-based conceptual framework. Using Braun and Clarke’s thematic analysis, five key themes emerged: (1) Exterior Identity and Visual Magnetism, (2) Intuitive Spatial Flow and Circulation, (3) Interactive Engagement and Hedonic Experience, (4) Staff as Co-Creators and Brand Ambassadors, and (5) Community Connection and Local Cultural Fit. Results show that experiential retail success depends on the synergy of aesthetic magnetism, seamless spatial planning, participatory engagement, and culturally responsive community-building. This integration transforms physical stores into immersive brand environments that reinforce global identity while resonating with local consumers, fostering emotional attachment, hedonic enjoyment, and purchase intention. By combining expert insights with existing literature, the study contributes a practical conceptual framework for global retailers seeking to merge universal brand identity with localized experiential strategies, offering guidance to achieve sustainable competitiveness in China’s dynamic retail market.